Draft Genome Sequences of Pseudoalteromonas telluritireducens DSM 16098 and P. spiralis DSM 16099 Isolated from the Hydrothermal Vents of the Juan de Fuca Ridge - Zhang, Huan (Genome Announc, 2016)
This report describes the draft genome sequences of two strains, Pseudoalteromonas telluritireducens DSM 16098 and P. spiralis DSM 16099, which were isolated from hydrothermal vents of the Juan de Fuca Ridge. The reads generated by an Ion Torrent PGM were assembled into contigs with total sizes of 4.4 Mb and 4.1 Mb for DSM 16098 and DSM 16099, respectively.